Granulated Bog Iron Ores as Sorbents in Passive (Bio)Remediation Systems for Arsenic Removal - Debiec, Klaudia; Rzepa, Grzegorz; Bajda, Tomasz; Uhrynowski, Witold; Sklodowska, Aleksandra; Krzysztoforski, Jan; Drewniak, Lukasz (Frontiers in Chemistry, 2018)
The main element of PbRS (passive (bio)remediation systems) are sorbents, which act as natural filters retaining heavy metals and carriers of microorganisms involved in water treatment. Thus, the effectiveness of PbRS is determined by the quality of the (ad)sorbents, which should be stable under various environmental conditions, have a wide range of applications and be non-toxic to (micro)organisms used in these systems. Our previous studies showed that bog iron ores (BIOs) meet these requirements. However, further investigation of the physical and chemical parameters of BIOs under environmental conditions is required before their large-scale application in PbRS. The aim of this study was (i) to investigate the ability of granulated BIOs (gBIOs) to remove arsenic from various types of contaminated waters, and (ii) to estimate the application potential of gBIOs in technologies dedicated to water treatment. These studies were conducted on synthetic solutions of arsenic and environmental samples of arsenic contaminated water using a set of adsorption columns filled with gBIOs. The experiments performed in a static system revealed that gBIOs are appropriate arsenic and zinc adsorbent. Dynamic adsorption studies confirmed these results and showed that the actual sorption efficiency of gBIOs depends on the adsorbate concentration and is directly proportional to them. Desorption analysis showed that As-loaded gBIOs are characterized by high chemical stability and they may be reused for the (ad)sorption of other elements, i.e. zinc. It was also shown that gBIOs may be used for remediation of both highly oxygenated waters and groundwater or settling ponds, where the oxygen level is low, as both forms of inorganic arsenic (arsenate and arsenite) were effectively removed. Arsenic concentration after treatment was <100 µg/L, which is below the limit for industrial water.